2017
DOI: 10.4103/ijmpo.ijmpo_98_16
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hormone receptor and human epidermal growth factor Receptor-2/neu expression in breast cancer with various clinicopathologic factors

Abstract: Background:A significant development in the breast carcinoma management is the correlation between the presence of hormone receptors in the tumor and response to hormonal therapy and chemotherapy. Human epidermal growth factor receptor-2/neu (Her-2/neu) overexpression also serves as a very useful parameter to predict response to herceptin.Aim of Study:The study was conducted to correlate immunohistochemical expression of markers such as estrogen receptor (ER), progesterone receptor (PR), and Her-2/neu with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
(59 reference statements)
6
13
1
Order By: Relevance
“…It was also seen that 23 cases (28.31%) were found to be triple negative breast cancers (TNBC). This was found to be in concordance with the findings of other similar studies [16,22,24] . As we know that Breast carcinoma is a heterogeneous disease with several clinical and histopathological presentations, this is due to several gene expression subtypes and molecular profiles.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It was also seen that 23 cases (28.31%) were found to be triple negative breast cancers (TNBC). This was found to be in concordance with the findings of other similar studies [16,22,24] . As we know that Breast carcinoma is a heterogeneous disease with several clinical and histopathological presentations, this is due to several gene expression subtypes and molecular profiles.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study we also found that HER2/Neu positivity (+3) was seen in 16 cases (19.75%) which was lower when compared to some studies [22,23,24] while it was higher that the study conducted by Shukla et al [16] . It was also seen that 23 cases (28.31%) were found to be triple negative breast cancers (TNBC).…”
Section: Discussionsupporting
confidence: 46%
“…Also Purdie et al reported that, ER-positive BC cases are more likely to be HER2-positive than PR-negative BC cases [29]. The expression of HER of 18.4% in the present study was similar to 18.5% which was reported in Brazil and lower than 40.7%, 24%, 23.1% and 22% that were reported in India, Ghana, Tanzania and Uganda [11,15,17,28]. Studies have shown that, expression of HER in both African American and African patients with BC is higher compared to Caucasians.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, the majority of breast cancer cases were hormone-dependent. A recent study conducted in India shows that 42.8% were oestrogen receptor-positive tumours and 31.8% were PR-positive [22]. Clearly, oestrogen is a carcinogen hormone.…”
Section: Discussionmentioning
confidence: 99%